Influence of Leather Fiber on Modulus of Elasticity in Bending Test and of Bend Strength of Particleboards - Renato Cardoso de Oliveira; Rodrigo Andraus Bispo; Mariana Ferreira Trevisan; Caroline Graminha Gilio; Felipe Reis Rodrigues; Sérgio Augusto Mello da Silva (Materials Research, 2021)
Abstract The society’s development provides consequences such as the increasing generation of industrial waste. In the city of Franca, São Paulo’s inland city, there are footwear industries that generate a large amount of leather waste during their production process. In most cases, there’s no use of this waste and they’re disposed of in landfills. A reuse alternative is the production of particleboards used in construction sectors. Therefore, one of the biggest challenges is the use of this leather waste adding value to the product and enabling the production of sustainable material. This work proposes the production of particleboards from Eucalyptus wood and leather fibers using castor oil polyurethane adhesive. In addition, the assessment of the leather fiber influence on modulus of rupture and elasticity obtained from a static bending test. The study investigated the proportion of 10%, 25% e 50% leather waste in relation to Eucalyptus particles and 10% castor oil polyurethane adhesive. The mechanical performance of the panels was evaluated based on ABNT NBR 14810-1 and 2 (2013; 2018). The results allowed us to ascertain that the incorporation of 10% leather waste in particleboard rated them, according to NBR 14810-1 and 2 (2013; 2018), as structural panels of type P4 for use in dry conditions.